Optimization of the Training Process of Highly Qualified Athletes in Athletics Combined Events at the Stage of Direct Preparation for Competitions - Vadym Adamchuk; Natalia Shchepotina; Viktor Kostiukevych; Olha Borysova; Viktoriia Bohuslavska; Valeria Tyshchenko; Vira Ovcharuk; Anna Bondar; Vadym Poliak (OVS LLC, 2023)
The purpose of the study was to develop an optimal model of the stage of direct preparation for competitions of highly qualified multieventers in athletics and experimentally justify its effectiveness. Materials and methods. 5 highly qualified multieventers, whose sports qualification is the Master of Sports of Ukraine, participated in the pedagogical experiment. The average age of the participants was (M±SD) 25.2±1.79 years. Research methods: theoretical analysis and generalization of data from literary sources; pedagogical experiment (the study was conducted from 2019 to 2021 according to the scheme of a sequential pedagogical experiment: from 2019 to 2020 - the ascertaining stage and from 2020 to 2021 - the formative stage); pedagogical observation of training and competitive activities; pedagogical testing (running 60 m from a high start, running 2 x 200 m with a rest interval of 1 min, triple jump from a standing position, throwing a ball with two hands from below on range, the running version of the PWC170(V) test was used for estimation of physical capacity and aerobic productivity of athletes); mathematical and statistical methods. Results. The total amount of training work of the studied multieventers at the stage of the formative experiment was reduced to 3148 min, compared to the ascertainment stage (4999 min), however, their intensity increased to an average of 6.11 points/min, compared to 5.72 points/min at the ascertainment stage. We managed to optimize the training process due to the developed models of microcycles at the stage of direct preparation for competitions, in which attention was focused on the leading types of each of the multieventers. Conclusions. Reducing the amount of load at the stage of direct preparation for competitions with a simultaneous increase in their intensity allowed the athletes to reach the peak of their sports form, as evidenced by the results of the main competitions of each of the athletes. The analysis of indicators of physical and functional fitness of highly qualified track and field athletes made it possible to establish that most of the results at the stage of the formative experiment improved statistically in a reliable way by an average of 2.6-6.5 %, which confirms the effectiveness of the proposed 8-week model of the stage of direct preparation for the competition and allows to recommend it for practical use in the training process of multieventers at the stage of maximum fulfillment of individual capabilities.